The hidden side of news diffusion: Understanding online news sharing as an interpersonal behavior. (November 2018) - Ihm, Jennifer; Kim, Eun-mee
Unlike previous approaches to online news sharing behaviors dealing with the dissemination of information to broader audiences, this article interprets that behavior as an act of relational communication. Drawing from surveys of 400 online news users, we examine how they manage their self-presentation and account for their audience's characteristics differently when they engage in online news sharing activities on mobile instant messenger (MIM) and social networking site (SNS). Our findings suggest that individuals who are highly motivated by self-presentation share news online more than others. Individuals also target different audiences, depending on their media environments. Specifically, SNS users are more cautious about their audiences' connections with other users. The implications are that news sharing behaviors are a type of communication used for forming relationships and managing impressions beyond informational purposes, based on active individuals' strategic considerations of their audiences' characteristics.